The Contexts, Paradoxes, and Rewards of Multidisciplinary Teaching - Twine, France Winddance; Parks, Lisa; Yasuda, Kim (Radical Teacher, 2023)
In the Fall of 2021 we co-taught a graduate seminar that launched a year long Mellon Sawyer series. In this essay, we reflect on the contexts, paradoxes and processes that informed our multidisciplinary collaboration teaching a Sawyer Seminar on Race, Migration and White Supremacy in California. We believed that it was vital to being with the migration experiences of Native Americans from rural areas to urban California. We sought to position American Indian migration histories as foundational to cultural and historical understandings of migration to California. Our account of our pedagogical practices details the rewards and realities of collaborative teaching at a public research university. We identify the paradoxes and tensions that we encountered as we developed a syllabus that did not simply "add and stir" different methodologies, histories or fields, but instead, synthesized theoretical and pedagogical across film, art and media studies, history and sociology.